Growth kinetics and wear resistance of vanadium carbide on AISI D2 steel produced by TRD process. (2nd March 2021) - Zhou, Lianpu; Zhu, Chundong; Guo, Lian; Wei, Zihao
Abstract: Vanadium carbide coating was obtained on the surface of AISI D2 steel by thermal reactive diffusion process using molten borax as based salt and vanadium pentoxide as vanadium donor. The process was performed at 900 °C, 940 °C, 980 °C and 1020 °C for 3 h, 4 h, 5 h and 6 h. The Optical Microscopy was used to observe the morphology of cross section of coating layer. Energy Dispersive Spectroscopy was used to analyse the element content of the matrix and the coating layer by spot scanning and line scanning. X-ray Diffraction was used to obtained the phase composition of the coating layer. Microhardness Tester was used to measure the Vickers hardness of the coating layer and matrix. Friction and wear tester were used to explore wear resistance of the coated and uncoated specimens. The results show that the thickness of vanadium carbide coating ranges from 7.54 μ m to 19.1 μ m under different treatment time and temperatures. The V8 C7 and VC x are the main phases contained in the vanadium coating layer. A thickness of about 3 μ m transition layer is between the matrix and coating layer and the transition layer has a block effect on the diffusion of iron. The growth rate constants of vanadium carbide coating layer at 900 °C, 940 °C, 980 °C and 1020 °C were obtained as (5.20 ± 0.116) ×10 –11 cm 2 s −1, (8.91 ± 0.253) ×10 –11 cm 2 s −1, (1.26 ± 0.020) ×10 –10 cm 2 s −1, and (1.70 ± 0.036) ×10 –10 cm 2 s −1 respectively. The activation energy for vanadium carbide layer is 123.3 ± 10.1 kJ mol −1 and the diffusion constant is (2.58 ± 1.96) ×10 –5 cm 2 s −1 . The maximum hardness of vanadium carbide coating layer on the surface of AISI D2 steel can reach 2594HV. The wear rate of untreated and treated specimens was evaluated as 15.58 × 10 –13 m 3 /(N·m), 5.63 × 10 –13 m 3 /(N·m) respectively and the wear resistance of treated specimens by TRD process was about 3 times than untreated specimens.